Risk Mitigation Analysis in the Construction of Dormitories for Students of Riyadlus Sholihin Islamic Boarding School, Probolinggo City - Aditya, Febri; Witjaksana, Budi; Sajiyo, Sajiyo (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The implementation of construction projects often faces various risks that can lead to delays, cost overruns, and decreased quality of work. One example occurred in the project to build a dormitory for students of the Riyadlus Sholihin Islamic Boarding School in Probolinggo City, which experienced a time deviation despite acceleration efforts. This shows the importance of implementing systematic risk management to identify and address potential risks from the beginning of project implementation. This study uses a descriptive quantitative approach through the dissemination of questionnaires and interviews to related parties in the project. The analysis was carried out using the Severity Index method to calculate the level of probability and impact of each risk, as well as the probability and impact matrix to determine the level of risk significance. The dominant risk is then further analyzed to determine mitigation actions. The results of the study showed five risks with a "Very High" level, namely the preparation of the wrong work method, poor coordination between parts, the accuracy of completing work within a certain duration, poor planning and scheduling, and low labor productivity. Mitigation strategies are developed to reduce the impact of these risks, including through training, improved communication, the use of planning software, and strengthening the monitoring system. This research makes a real contribution to the risk management of construction projects in a more effective and structured manner.